Convenient methodology for extraction and subsequent selective propagation of mouse melanocytes in culture from adult mouse skin tissue - Tomonobu, Nahoko (Biochem Biophys Rep, 2019)
Mouse melanoma B16-BL6 cells are useful cells for cancer metastatic studies. To understand the metastatic principle at molecular levels, it is necessary to carry out experiments in which cancer cells and their normal counterparts are compared. However, unlike normal human melanocytes, preparation of normal mouse melanocytes is quite difficult due to the lack of marketing and insufficient information on an established protocol for primary culture of mouse melanocytes. In this study, we aimed to establish a convenient method for primary culture of mouse melanocytes on the basis of the protocol for human melanocytes. The main obstacles to preparing pure mouse melanocytes are how to digest mouse skin tissue and how to reduce the contamination of keratinocytes and fibroblasts. The obstacles were overcome by collagenase digestion for skin specimens, short time trypsinization for separating melanocytes and keratinocytes, and use of 12-O-Tetradecanoylphorbol 13-acetate (TPA) and cholera toxin in the culture medium. These supplements act to prevent the proliferation of keratinocytes and fibroblasts, respectively. The convenient procedure enabled us to prepare a pure culture of normal mouse melanocytes. Using enriched normal mouse melanocytes and cancerous B16-BL6 cells, we compared the expression levels of melanoma cell adhesion molecule (MCAM), an important membrane protein for melanoma metastasis, in the cells. The results showed markedly higher expression of MCAM in B16-BL6 cells than in normal mouse melanocytes.